If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 = -3 + 2(2x + -2) Reorder the terms: 1 = -3 + 2(-2 + 2x) 1 = -3 + (-2 * 2 + 2x * 2) 1 = -3 + (-4 + 4x) Combine like terms: -3 + -4 = -7 1 = -7 + 4x Solving 1 = -7 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 1 + -4x = -7 + 4x + -4x Combine like terms: 4x + -4x = 0 1 + -4x = -7 + 0 1 + -4x = -7 Add '-1' to each side of the equation. 1 + -1 + -4x = -7 + -1 Combine like terms: 1 + -1 = 0 0 + -4x = -7 + -1 -4x = -7 + -1 Combine like terms: -7 + -1 = -8 -4x = -8 Divide each side by '-4'. x = 2 Simplifying x = 2
| -8y=20+3x | | 6-(-2+5y)= | | -5=8m+12 | | 0.5x+3=0.66666666666x+1 | | 0=200x-400x-300x+400x-500000-444444+27264234 | | 2n+18=4n | | 6-(-a)= | | 4x-3(2x-5)= | | 46-3x=10-9x | | 6x+7=-47-3x | | 7x-12=6x+6 | | 9+4=141 | | 3a-(a-b)= | | -4x-3+(-3x-4)=28 | | 2a-(a+b)= | | isk-3k=6k+5-8k | | 8y-(6y-3)= | | 4x^3+3x^2+3x-1=0 | | 6x+5(20-2x)=12 | | y=lg(x^2-7x+10) | | 3+(-1)*b= | | 0=18000x-450x-5000x-400000-500000 | | x^2-13x+10=0 | | 4x-2xy=7 | | (1)*b= | | 18-27y+10y^2=0 | | (12+3)xy= | | 6xy-3x-2y=55 | | 23423423423423y=238472384672354276345723542365443628723423y | | 123123y+81723981273=283791y+12312 | | -15-(-26)= | | 10=-3x-x^2 |